Perencanaan Sumber Daya Manusia Pada Rumah Sakit Ibu dan Anak dr Djoko Pramono - Prawiro, Daniel Septo; Suroso, Suroso; Anggela, Flora Patricia (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
Internship is a compulsory subject in the form of student work practice placement activities, to provide insight into the application of knowledge in the business / work world. Students practice their abilities and knowledge in analyzing problems related to the field of study program that occurs in the world of work / business. RSIA Dr. Djoko Pramono is a development of the Singapore Maternity Hospital, which has been serving the Karawang community since 1993. In accordance with its commitment to further improve service quality, and also meet the demands of the community, since March 7, 2007, RB Singaperbangsa officially increased its status to RSB Dr. Djoko Pramono, which is the first specialty hospital in the city of Karawang, and on February 1, 2010 became RSIA (Mother & Child Hospital). The method used in this research is descriptive and library research. Based on the results of practical work on Human Resource Planning at RSIA dr. Djoko Pramono it can be concluded that the Human Resource Planning in the company has not been implemented properly. Because there are still many employees from several work units whose number of employees is not yet effective.